Gaya Kepemimpinan Kepala Desa Ongulero Kecamatan Marawola Barat Kabupaten Sigi - Reza, Fachrul (Badan Riset dan Inovasi Daerah Sulawesi Tengah, 2023)
Abstract Leadership is a person's ability to position himself according to space and time and be able to understand what is his duty and responsibility, so that satisfactory results are obtained for achieving good employee performance. Therefore a village head must know and be able to play his role as a leader in his village. The purpose of this study was to find out how the leadership style of the Head of Ongulero Village, Marawola Barat District, Sigi Regency. The informants in this study were the Ongulero Village office staff. then the informants are the Village Secretary, Head of Government, Head of Development, Community. The results of the study show that to find out the leadership style in carrying out its duties and functions at the Ongulero Village office, Marawola Barat District, Sigi Regency. The author chooses a theory that is considered more suitable to be applied to government organizations, in this case Ongulero Village, West Marawola District, Sigi Regency, is the theory of Harbani Pasoloang (2008: 50-51), namely: Instruction, Consultation, Participation, Delegation. So it can be concluded that the author concludes that the Leadership Style of the Head of Ongulero Village, West Marawola District, Sigi Regency as measured from the four indicators, what is considered to have gone well is the Instruction indicator/dimensional, whereas in the Consultation, Participation and Delegation indicators/dimensions the results are not running well. Abstrak Kepemimpinan merupakan kemampuan seseorang dalam memposisikan diri sesuai ruang dan waktu serta dapat memahami apa yang menjadi tugas dan tanggung jawabnya, sehingga diperoleh hasil yang memuaskan untuk tercapainya kinerja pegawai dengan baik. Oleh sebab itu seorang kepala desa harus tahu dan mampu memainkan perannya sebagai seorang pemimpin didesanya. Tujuan penelitian ini adalah Untuk mengetahui Bagaimana Gaya Kepemimpinan Kepala Desa Ongulero Kecamatan Marawola Barat Kabupaten Sigi. Informan dalam penelitian ini adalah perangkat kantor Desa Ongulero. maka informan yaitu Sekretaris Desa, Kaur Pemerintahan, Kaur Pembangunan, Masyarakat. Hasil penelitian menunjukkan bahwa Untuk mengetahui gaya kepemimpinan dalam melaksanakan tugas dan fungsinya dikantor Desa Ongulero Kecamatan Marawola Barat Kabupaten Sigi. Penulis memilih Teori yang dianggap lebih cocok diterapkan pada organisasi pemerintahan dalam hal ini Desa Ongulero Kecamatan Marawola Barat Kabupaten Sigi, adalah teori Harbani Pasoloang (2008: 50-51), yakni: Instruksi, Konsultasi, Partisipasi, Delegasi. Maka dapat disimpulkan Penulis mengambil kesimpulan bahwa Gaya Kepemimpinan Kepala Desa Ongulero Kecamatan Marawola Barat Kabupaten Sigi yang diukur dari keempat indikator tersebut, yang dinilai sudah berjalan dengan baik adalah indikator/dimensi Instruksi, sedangkan dalam indikator/dimensi Konsultasi, Partisipasi dan Delegasi yang hasilnya kurang berjalan dengan baik